A comparative analysis of generic prescribing patterns among teaching and non-teaching clinicians in Nellore, India - Choudary Gorantla, Naveen; Penupothu, Sree Nagamani (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The aim was to study the prescribing patterns of clinicians working in two different settings i.e. Teaching clinicians (clinicians working in teaching hospital) and Non-teaching clinicians (clinicians involved only in private practice). Methods: A comparative cross sectional study was carried out for a period of 6 months in two settings. The study is confined to teaching clinicians comprising of qualified medical practitioners in ACSR Government Medical College (ACSR GMC) and Non-teaching clinicians of qualified medical practitioners in private health sector (PMPs). 450 prescriptions were collected from clinicians belonging to various departments of ACSR GMC and 450 prescriptions from private practitioners of Nellore city. Data was coded and entered in MS Excel. Data was analyzed on EPI INFO version 3.5.4. Results: In this study it was found that teaching clinicians prescribed 146 (12.85%) drugs by generic name, whereas non-teaching clinicians prescribed 112 (8.75%) drugs by generic name. Conclusions: The findings of the present study indicate that the drugs prescribed by the generic names were remarkably less in both teaching and non teaching clinicians. This indicates a need for improving the generic prescribing patterns in both the settings.